PERSONNEL DEVELOPMENT OF INNOVATIVE-ACTIVE ENTERPRISE AS AN OBJECT OF MANAGEMENT IN INCREASING COMPETITIVENESS - BABCHYNSKA ОLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Personnel development is a complex economic concept, which is proposed to be understood as the management activities of the enterprise, which involves the formation and increase of quality professional, social, personal characteristics of staff to ensure the current and strategic goals of the enterprise. In addition, staff development is a process consisting of a series of successive stages. In the structure of personnel development of the enterprise it is expedient to separate professional, social, personal directions which have various tasks, and at the same time are elements of a uniform complex of actions having common methods of realization of tasks. The basis of development is professional development, which is proposed to understand the process of formation and increase of professional potential of employees of the enterprise, due to the acquisition of qualitatively new characteristics for the maximum realization of human abilities in professional activities. The peculiarities of forming an effective management system of development and use of the enterprise’s personnel are investigated. Some measures to improve the effectiveness of the management process of development and use of personnel are proposed. The scientific approaches concerning formation of the mechanism of management of development and use of personnel are considered. The task of personnel development management of an innovatively active enterprise is to ensure compliance of quantitative and qualitative characteristics of personnel with the existing needs of the enterprise at the moment; development of innovative potential of the enterprise personnel. The innovative potential of an innovatively active enterprise should be understood as objective opportunities to maximize the intellectual potential of employees to achieve goals, as well as a set of tools, sources, opportunities and abilities, the use of which is aimed at solving any problems in innovation. The support system contributes to the realization of the goal of personnel development management of an innovatively active enterprise, by providing the necessary resources and creating the appropriate prerequisites.